Multicomponent Domino Cyclization of Ethyl Trifluoropyruvate with Methyl Ketones and Amino Alcohols as A New Way to γ-Lactam Annulated Oxazacycles - Marina V. Goryaeva; Olesya A. Fefelova; Yanina V. Burgart; Marina A. Ezhikova; Mikhail I. Kodess; Pavel A. Slepukhin; Vasily S. Gaviko; Victor I. Saloutin (Molecules, 2023)
A new route to bicyclic γ-lactams was found, which was proposed as a three-component cyclization of ethyl trifluoropyruvate with methyl ketones and 1,2-, 1,3-amino alcohols. As a result, a series of trifluoromethyl-substituted tetrahydropyrrolo [2,1-b]oxazol-5-ones and tetrahydropyrrolo[2,1-b][1,3]oxazine-6-ones was synthesized, in which the substituent at the nodal carbon atom was varied. The introduction of a twofold excess of ethyl trifluoropyruvate in reactions with amino alcohols and acetone made it possible to obtain the same bicycles, but functionalized with a hydroxyester fragment, which are formed due to four-component interactions of the reagents. Transformations with 2-butanone and aminoethanol lead predominantly to similar bicycles, while an analogous reaction with aminopropanol gives N-hydroxypropyl-2,3-dihydropyrrol-5-one. Almost all bicycles are formed as two diastereomers, the structure of which was determined using 1H, 19F, 13C NMR spectroscopy, including two-dimensional experiments and XRD analysis. A domino mechanism for the formation of tetrahydropyrrolo[2,1-b]oxazacycles was proposed, which was confirmed by their stepwise synthesis through the preliminary preparation of the aldol and bis-aldol from ethyl trifluoropyruvate and methyl ketones.